A Study of recurrent grammatical errors in writing English among undergraduates - Sarmatha, S. (Faculty of Humanities and Social Sciences, University of Sri Jayewardenepura., 2016)
Writing in English is a mode of written communication and it is an important part of academic writing at tertiary level. In the writing process, a student expresses his/her thoughts and ideas on a particular subject through words and sentences. There is a need to collect the facts and then organize them in an order before writing. Undergraduates need to send e-mails, submit research proposal and papers, and write essays, official letters, business letters, reports, minutes and projects. having good writing skills in English helps students to gain good results in the university examinations and assignments. Students should pay attention to language elements such as vocabulary, grammatical structure, punctuation and spellings when they write. Lecturers have to develop students’ writing skills which is useful for their current and future disciplines. Some mistakes in writing English frequently occur among undergraduates at the University of Jaffna both in examination and assignments. The objective of this study was to find out the recurrent grammatical errors in writing and to analyze the errors with the view to understanding the errors and assisting to improve the students’ writing skills and create more efficiency at tertiary level. the experimental part of the paper dealt with the recurrent grammatical errors in writing English among the undergraduates of the Faculty of Arts, University of Jaffna. This study was based on qualitative and descriptive methodologies. The samples used in this study were collected from the assignment materials such as journal entries, reports, letters and minutes written by students of Humanities and Social Sciences in the Faculty of Arts, University of Jaffna. This study investigated the most common grammatical mistakes found in the student writings and analyzed them. Through this study, the researcher found out the constraints faced by the students when they were engaged in writing in English. The analysis explored the underlying reasons for these common errors which will contribute to the field of language teaching.
Keywords: Recurrent grammatical errors; Writing skills; Constraints; Grammatical structure